Typification of names in the group Coerulans of the genus Sesleria (Poaceae) - Kuzmanovic, Nevena; Barina, Zoltan; Šida, Otakar; Lakušić, Dmitar (Phytotaxa, 2015)
In this paper we typify and discuss twelve names belonging to group Coerulans in the genus Sesleria (Poaceae). The holotype is established for S. tenerrima, and lectotypes are designated for the names S. bielzii, S. coerulans, S. coerulans var. borsae, S. comosa, S. klasterskyi, S. korabensis var. mrkvickana, S. krajinae, S. orbelica and S. orbelica var. pirinensis. Neotypes are selected for the names S. comosa var. weberii and S. haynaldiana. Images are provided for nine specimens selected here as types that are not available online. Previously published typifications for other names in the Coerulans group are summarized.